"Maybe we did not learn that much academically, but we learn more from experience" – Erasmus mobility and its potential for transformative learning. (March 2022) - Nada, Cosmin I.; Legutko, Justyna
Abstract: Mobility experiences in higher education are usually met with great enthusiasm and are often described as sources of (transformative) learning. At the same time, less optimistic perspectives are brought forward by scholars who question the intrinsic value of international mobility in terms of encouraging personal growth and the acquisition of an intercultural and international mindset. In this article, retrospective accounts of Erasmus alumni, gathered several years after their sojourn, are analysed to understand the extent to which engaging in an international exchange during one's university years can have long-lasting and transformative learning effects. The findings indicate that participating in an Erasmus exchange can indeed enhance personal growth and lead to transformative learning. Such an experience can give rise to significant changes in young people's future decisions that may involve, for instance, more internationally oriented aspirations, a better understanding of cultural diversity, or an interest in engaging with new international experiences, as a result of the initial Erasmus exchange.